ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PELAPORAN PERUSAHAAN INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2019 DAN 2020 - Totok Susilo Pamuji Nugroho; Fatihah Khoirin Hasanah (STIE Atma Bhakti, 2022)
The research aims to determine the effect of good corporate governance, liquidity, company age, and leverage on the timeliness of reporting on basic and chemical on the Indonesia Stock Exchange in 2019 and 2020. The population in this study were 79 companies and 64 companies that be sampled. In this study, good corporate governance is measured using institusional ownership, liquidity is measured by the current ratio (CR), company age is measured by the distance between the year of research and the year of establishment and leverage is measured by total debt divided by total assets. The data collected were secondary data and the sampling technique of this study uses logistic regression with a significance level of 0.05. Based on the results of the study, it was stated that good corporate governance had a significant effect on reporting timeliness of 0.021 < 0.05. While liquidity does not affect the timeliness of reporting by 0.233 > 0.05, company age does not affect the timeliness of reporting by 0.403 > 0.05 and leverage does not affect the timeliness of reporting by 0.384 > 0.05.